2014
DOI: 10.1371/journal.pone.0102331
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of the Response to Interferon Beta in Epstein-Barr-Transformed and Primary B Cells of Patients with Multiple Sclerosis

Abstract: The effects of interferon-beta (IFN-β), one of the key immunotherapies used in multiple sclerosis (MS), on peripheral blood leukocytes and T cells have been extensively studied. B cells are a less abundant leukocyte type, and accordingly less is known about the B cell-specific response to IFN-β. To identify gene expression changes and pathways induced by IFN-β in B cells, we studied the in vitro response of human Epstein Barr-transformed B cells (lymphoblast cell lines-LCLs), and validated our results in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 77 publications
0
24
1
Order By: Relevance
“…The present results also suggested the possibility that certain ISGs upregulated only in limited cell types are activated through cell type‐specific downstream signaling pathways after the immediate activation of common IFN signaling pathway. A recent microarray‐based gene expression study identified a panel of in vitro ISGs, such as NEXN, DDX60L, IGFBP4, HAPLN3, CD79B, SYK LAG3 and IL27RA in human Epstein–Barr virus‐transformed B cells . We identified NEXN, DDX60L, IGFBP4 and HAPLN3 as the set of in vivo ISGs in purified populations of B cells of IFNβ‐treated MS patients (Table S5).…”
Section: Discussionmentioning
confidence: 91%
“…The present results also suggested the possibility that certain ISGs upregulated only in limited cell types are activated through cell type‐specific downstream signaling pathways after the immediate activation of common IFN signaling pathway. A recent microarray‐based gene expression study identified a panel of in vitro ISGs, such as NEXN, DDX60L, IGFBP4, HAPLN3, CD79B, SYK LAG3 and IL27RA in human Epstein–Barr virus‐transformed B cells . We identified NEXN, DDX60L, IGFBP4 and HAPLN3 as the set of in vivo ISGs in purified populations of B cells of IFNβ‐treated MS patients (Table S5).…”
Section: Discussionmentioning
confidence: 91%
“…It has yet only been part of some genome-wide siRNA screens on HIV host factors (59), nonalcoholic fatty liver disease (60), and childhood obesity (61) and was identified in a genome-wide association study as a biomarker for the antidepressant responses of selective serotonin reuptake inhibitors (62). DDX60L has also been recognized as an ISG product before in a study searching for genes induced by IFN-␤ in Epstein-Barr virus-infected multiple sclerosis patients (24). However, it was not included in two previous comprehensive functional analyses of potential effector proteins involved in the interferon response against HCV (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed to partially overlapping sets of genes mediating type I, type II, and type III IFN responses (6). In addition, DDX60L had been previously described as a type I IFN response gene, similar to DDX60 (24). Therefore, we were interested in whether DDX60L also significantly contributes to type I and type III IFN responses against HCV.…”
Section: Impact Of Ifn-␥ On Hcv Replication In Huh6 and Huh-7 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX60L is likely to be highly specific in its antiviral functions, as it was unable to inhibit replication of hepatitis A virus, regardless of its similarity to HCV [71]. In addition, it is noteworthy to mention that DDX60L is also upregulated in IFN-β-treated EpsteinBarr-transformed B cells derived from multiple sclerosis patients [174].…”
Section: Ddx60lmentioning
confidence: 99%